2017
DOI: 10.1155/2017/2715092
|View full text |Cite
|
Sign up to set email alerts
|

Development of Electrohydraulic Forming Process for Aluminum Sheet with Sharp Edge

Abstract: Electrohydraulic forming (EHF), high-velocity forming technology, can improve the formability of a workpiece. Accordingly, this process can help engineers create products with sharper edges, allowing a product's radius of curvature to be less than 2 mm radius of curvature. As a forming process with a high-strain rate, the EHF process produces a shockwave and pressure during the discharge of an electrical spark between electrodes, leading to high-velocity impact between the workpiece and die. Therefore, the obj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…The expansion of the plasma channel in the surrounding medium is due mainly to the rapid and pronounced pressure increase in the spark channel between the electrodes, caused by the temperature rise during the rapid and high energy input [9]. This process takes place in a time interval of less than 100 µs in most cases [11,12]. The shock wave caused by the expansion of the plasma channel is transmitted to the surrounding medium as a pressure wave and then propagates in this at the speed of sound, which is 1500 m/s in water [7].…”
Section: Introductionmentioning
confidence: 99%
“…The expansion of the plasma channel in the surrounding medium is due mainly to the rapid and pronounced pressure increase in the spark channel between the electrodes, caused by the temperature rise during the rapid and high energy input [9]. This process takes place in a time interval of less than 100 µs in most cases [11,12]. The shock wave caused by the expansion of the plasma channel is transmitted to the surrounding medium as a pressure wave and then propagates in this at the speed of sound, which is 1500 m/s in water [7].…”
Section: Introductionmentioning
confidence: 99%
“…When a sheet metal is deformed under highspeed conditions, the formability is improved by the diesheet interaction and the inertia effect of the sheet. Many researchers have demonstrated the improvement of the formability through various experiments and finite element analyses [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have found that the high-velocity forming process can improve the formability of a sheet metal having low formability, such as magnesium alloys, titanium alloys, and some aluminum alloys [1]. Shim and Kang [2] used the 5000 series of aluminum alloys for the EHF experiment and showed formability improvement in the EHF process by comparing Forming limit diagrams (FLDs) in quasi-static and high-speed conditions. Gillard et al [3] and Golovashchenko et al [4,5] showed that the formability of the DP 980 sheet was improved by die–sheet interactions in the EHF experiment using dies of various shapes.…”
Section: Introductionmentioning
confidence: 99%